Self-selection of Male Circumcision Clients and Behaviors following Circumcision in a Service Program in Rakai, Uganda - Kagaayi, Joseph; Kong, Xiangrong; Kigozi, Godfrey; Ssekubugu, Robert; Kigozi, Grace; Nalugoda, Fred; Serwadda, David; Wawer, Maria J.; Gray, Ronald H. (AIDS (London, England), 2016)
Sub-Saharan African countries have substantially scaled-up safe male circumcision (SMC) services. However, it is unclear whether services are reaching men most at risk of HIV and whether there is behavioral disinhibition after SMC. We compared characteristics of SMC acceptors and non-acceptors in Rakai, Uganda. Cohort design Through the Rakai Community Cohort Study, baseline characteristics of 587 non-Muslim men who subsequently accepted SMC were compared to those of 4,907 uncircumcised non-Muslim men. Behaviors after SMC were compared with those of men who remained uncircumcised. Poisson multivariable regression was used to estimate adjusted prevalence rate ratios (aPRR) of behaviors in circumcised versus uncircumcised men.
Keywords: Circumcision; Self-selection; Risk compensation; Rakai; Uganda